Analysis on subdivision technical practice between Malaysia and Thailand in cadastral application / Muhammad Afiq Ikhwan Hamidi - Hamidi, Muhammad Afiq Ikhwan (2019)
This paper describes the procedure of subdivision technical practice between Malaysia and Thailand in cadastral application. The objectives of this research is to study the procedure of subdivision technical practice in cadastral perspective in Malaysia and Thailand. To analyse the different of subdivision technical practice between Malaysia and Thailand and to present the most relevance procedure to deal with subdivision survey practice in current trends. This research start with research planning, data collection and data analysis. This research will compare the difference on subdivision technical practice between Malaysia and Thailand on three main aspects, which is preparatory work, fieldwork and data processing method. This research also helps the relevancy of current procedure with the today trends. The main data used for this study is National Land Code (NLC) 1965, Land Code 1954 (BE45), Circular from Director of Department of Survey and Mapping Malaysia (DSMM) and survey procedure requirement from Department of Land (DOL) Thailand. Lastly, Questionnaire is distributed to determine the most relevance procedure of technical practice in current trends to archive the last objective.